Effects of a proprioceptive focal stimulation (Equistasi®) on reducing the biomechanical risk factors associated with ACL injury in female footballers - Spolaor, Fabiola; Guiotto, Annamaria; Ciniglio, Alfredo; Cibin, Federica; Sawacha, Zimi (Frontiers in Sports and Active Living, 2023)
Introduction Football presents a high rate of lower limb injuries and high incidence of Anterior Cruciate Ligament (ACL) rupture, especially in women. Due to this there is the need to optimize current prevention programs. This study aims to verify the possibility to reduce the biomechanical risk factors associated with ACL injury, through the application of proprioceptive stimulation by means of the Equistasi® device. Methods Ten elite female footballers were enrolled and received the device for 4 weeks (5 days/week, 1h/day). Athletes were assessed directly on-field at four time points: T0 and T1 (evaluation without and with the device), T2 (after 2 weeks), T4 (after 4 weeks) while performing two different tasks: Romberg Test, and four sidestep cutting maneuvers bilaterally. Seven video cameras synchronized with a plantar pressure system were used, thirty double colored tapes were applied on anatomical landmarks, and three dimensional coordinates reconstructed. Vertical ground reaction forces and center of pressure data were extracted from the plantar pressure insoles. Hip, knee, and ankle flexion-extension angles and moments were computed as well as abd-adduction joint torques. From the Romberg Test both center of pressure descriptive variables and frequency analysis parameters were extracted. Each variable was compared among the different time frames, T1, T2 and T4, through Friedman Test for non-parametric repeated measures (p<0.05); Wilcoxon Signed Rank Test was used for comparing variables between T0 and T1 (p<0.05) and across the different time frames as follows: T1–T2, T2–T4 and T1–T4. Results Statistically significant differences in both posturographic and biomechanical variables between the assessment at T0 and T1 were detected. Reduced hip and knee abduction torques were revealed in association with reduced both ground reaction forces and ankle dorsiflexion torque from T1 up to T4. Discussion The proprioceptive stimuli showed to have the potential to improve cutting biomechanics mainly with respect to the ligament and quadriceps dominance theories. Results of the present study, even if preliminary and on a small sample size, could be considered promising towards the inclusion of proprioceptive training in injury prevention programs.